2020
DOI: 10.3390/ma13071662
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surface Roughness and Defect Formation after The Machining of Sintered Aluminum Alloy AlSi10Mg

Abstract: This article presents selected issues related to the workpiece surface quality after machining by the laser sintering of AlSi10MG alloy powder. The surfaces of the workpiece were prepared and machined by longitudinal turning with tools made of sintered carbides. The occurrence of breaches on the machined material surface was found, which negatively influence the values of 3D surface roughness parameters. The occurring phenomena were analyzed and proposals for their explanation were made. Guidelines for the mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…The analysis of down-milling and up-milling of sintered material and roughness, topography and microscopic measurements of the machined surface were carried out. The results presented in the paper are a continuation of the analyses undertaken by the authors as previously described [ 41 ].…”
Section: Introductionmentioning
confidence: 58%
“…The analysis of down-milling and up-milling of sintered material and roughness, topography and microscopic measurements of the machined surface were carried out. The results presented in the paper are a continuation of the analyses undertaken by the authors as previously described [ 41 ].…”
Section: Introductionmentioning
confidence: 58%
“…Several studies have found that 3D surface topography parameters provide more exact information about the surface quality than the 2D parameters, e.g., [ 10 , 11 ] and this statement was recently confirmed by studies carried out typically for their comparison [ 12 , 13 ]. In the present study the topography measurements were carried out by optical equipment, whose reliability is higher than that of the conventional stylus solution [ 14 ].…”
Section: Introductionmentioning
confidence: 88%
“…In this case, more favorable results were obtained for samples made by SLM. A similar set of samples (AlSi10Mg, casting / DMLS) was used by Struzikiewicz et al [22], who proved that in the case of orthogonal turning of laser sinters, products of lower surface finish are obtained. The problem was the appearance of burrs and chipping that adhered to the treated surface, reducing its quality.…”
Section: Introductionmentioning
confidence: 99%